Believing the Reality of God through Love for God According to Deuteronomy 6:1-25 - Simanjuntak, Harlinton; Panggabean, Kristina A. M. (Sekolah Tinggi Teologi Trinity Parapat, 2024)
This article examine the people of Israel were able to express their faith in the One God by their acts of love for God. The theological themes that include confession of faith, the election of Israel, the covenant, and the existence of God in history. Confession of faith refers to acknowledging the LORD as their God. Believing in the only God shown through love for God was expressed by the Israelites by doing, keeping all God's statutes and doing them faithfully. They must depend on and fear to LORD, which is the strongest foundation to hold on. The love expressed through obedience would benefit them and their descendants. God loves His people. Christians should love God with all their heart, soul and strength. In daily life, Christians should show love for the only God. Love can be shown by teaching the word of God to children, so that they also become Christians who believe in Jesus Christ as their personal Lord and Savior. The research method used is a literature study research method, with an exegesis approach. The exegesis study was conducted to find out the meaning of the text of Deuteronomy 6:1-25.